2008
DOI: 10.1016/j.jacc.2008.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Clinical Impact of Dual Nonresponsiveness to Aspirin and Clopidogrel in Patients With Drug-Eluting Stents

Abstract: Dual nonresponsiveness to aspirin and clopidogrel is a relatively infrequent condition that identifies patients at a very high risk of DES thrombosis or death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
2
9

Year Published

2009
2009
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 188 publications
(129 citation statements)
references
References 27 publications
7
111
2
9
Order By: Relevance
“…61 Dual resistance to aspirin and clopidogrel at the time of drug-eluting stent implantation is associated with an 11% risk of definite or probable stent thrombosis at 6 months compared to only 2% in responders. 62 Würtz et al 63 examined the antiplatelet effects of aspirin in patients with a confirmed history of stent thrombosis compared to those without such a history and found increased platelet aggregation in patients with a history of thrombosis. Those with a history of stent thrombosis had a higher but nonsignificant fraction of immature platelet cells, suggesting that rapid platelet turnover may, in part, contribute to the heightened aspirin resistance in this population.…”
Section: History Of Stent Thrombosismentioning
confidence: 99%
“…61 Dual resistance to aspirin and clopidogrel at the time of drug-eluting stent implantation is associated with an 11% risk of definite or probable stent thrombosis at 6 months compared to only 2% in responders. 62 Würtz et al 63 examined the antiplatelet effects of aspirin in patients with a confirmed history of stent thrombosis compared to those without such a history and found increased platelet aggregation in patients with a history of thrombosis. Those with a history of stent thrombosis had a higher but nonsignificant fraction of immature platelet cells, suggesting that rapid platelet turnover may, in part, contribute to the heightened aspirin resistance in this population.…”
Section: History Of Stent Thrombosismentioning
confidence: 99%
“…If one may accept this threshold as a reference for resistance, the incidence seems to vary about 10%-20% in stable coronary artery disease, but reaches almost 50% in acute coronary syndromes [2]. In a study on the impact of dual non-responsiveness and the drug eluting stent implantation on the incidence of stent thrombosis, this dual non-responsiveness was identified in 6% of patients [24].…”
Section: Discussionmentioning
confidence: 99%
“…Collagen binds to the GPVI and GPⅠa/Ⅱa platelet receptors inducing granule release and TXA2 generation. Recently, RPR identified by collagen aggregation in ACS patients on ASA has been reported associated with cardiovascular events [67,68] and with the polymorphism C807T predisposing to MACE [69] . Collagen induced platelet aggregation can be impaired in different condition of platelet function disorders, such as: Glanzmann's thrombastenia, abnormalities of the signal-transduction pathways caused by COX-1 deficiency (aspirin like defect) or defects of platelet granules (α and/or δ storage pool deficiency) [42] .…”
Section: Platelet Aggregation On Platelet-rich Plasmamentioning
confidence: 99%